Genetic Engineering, Biofertilisation, Soil Quality and Organic Farming - Lichtfouse, Eric.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
Sustainable agriculture is a rapidly growing field aiming at producing food and energy in a sustainable way for humans and their children. Sustainable agriculture is a discipline that addresses current issues such as climate change, increasing food and fuel prices, poor-nation starvation, rich-nation obesity, water pollution, soil erosion, fertility loss, pest control, and biodiversity depletion. Novel, environmentally-friendly solutions are proposed based on integrated knowledge from sciences as diverse as agronomy, soil science, molecular biology, chemistry, toxicology, ecology, economy, and social sciences. Indeed, sustainable agriculture decipher mechanisms of processes that occur from the molecular level to the farming system to the global level at time scales ranging from seconds to centuries. For that, scientists use the system approach that involves studying components and interactions of a whole system to address scientific, economic and social issues. In that respect, sustainable agriculture is not a classical, narrow science. Instead of solving problems using the classical painkiller approach that treats only negative impacts, sustainable agriculture treats problem sources. Because most actual society issues are now intertwined, global, and fast-developing, sustainable agriculture will bring solutions to build a safer world. This book series gathers review articles that analyze current agricultural issues and knowledge, then propose alternative solutions. It will therefore help all scientists, decision-makers, professors, farmers and politicians who wish to build a safe agriculture, energy and food system for future generations.
Avidin and Plant Biotechnology to Control Pests -- Cover Crops for Sustainable Agrosystems in the Americas -- Cover Crops in Agrosystems: Innovations and Applications -- Improving Bioavailability of Phosphate Rock for Organic Farming -- Mixed Cropping and Suppression of Soilborne Diseases -- Decreasing Nitrate Leaching in Vegetable Crops with Better N Management -- Manure Spills and Remediation Methods to Improve Water Quality -- Cropping Systems Management, Soil Microbial Communities, and Soil Biological Fertility -- Cyanobacterial Reclamation of Salt-Affected Soil -- Measuring Environmental Sustainability of Intensive Poultry-Rearing System -- Compost Use in Organic Farming -- Beneficial Microorganisms for Sustainable Agriculture -- Foliar Fertilization for Sustainable Crop Production.
Keywords: Life sciences; Agriculture; Endangered ecosystems; Botany; Climatic changes; Soil conservation; Sustainable development; Life Sciences; Agriculture; Sustainable Development; Plant Sciences; Climate Change; Ecosystems; Soil Science & Conservation